Penyampaian Informasi Pada Pasien Wanita Tentang Pemakaian dan Penyimpanan Obat Intravaginal di Salah Satu Puskesmas Banjarmasin - Achyadi, Ryan; Muliani, Putri Sari; Muthia, Okta; Setiawan, Deni; Hakim, Ade Syarif (Jurnal Pelayanan dan Pengabdian Kesehatan untuk Masyarakat, 2024)
Infections in the female reproductive system are prevalent among women of reproductive age every year. These infections can lead to cervical cancer and infertility. There are two types of infections in the female reproductive system: sexually transmitted infections and infections caused by the abnormal growth of normal flora, known as vaginitis. The objective of this activity is to enhance the knowledge of female patients regarding the use of intravaginal medications in the Gadang Hanyar Community Health Center environment.The activity took place on Tuesday, April 29, 2023, at the Gadang Hanyar Community Health Center. Education was provided through lectures and the distribution of leaflets to participants. There was an improvement in participants' knowledge regarding the use of intravaginal medications. This is evident from the increase in the average pretest score (before education) from 56.66 to 82.5 for the average posttest score (after education). The health promotion regarding the use of intravaginal medications successfully enhanced respondents' knowledge about the correct usage and storage of intravaginal medications